RISK MANAGEMENT ANALYSIS OF BROILER FARMING IN WEST ACEH DISTRICT - Keumala Fadhiela ND; Rosa (RADJA PUBLIKA, 2025)
This study is to examine risk management techniques in broiler chicken production within West Aceh Regency. Broiler production is a rapidly yielding agricultural enterprise, although it is susceptible to production and financial hazards, such as disease outbreaks, fluctuations in feed prices, and mortality rates. Employing a case study methodology, primary data were gathered via field observations, structured interviews, and documentation from one of the largest independent broiler farms in the area. Data were examined with descriptive techniques, income assessment, and quantitative risk metrics including Coefficient of Variation (CV) and Feed Conversion Ratio (FCR). The analysis demonstrated that the average mortality rate (8,1%) beyond the industry tolerance threshold (3–5%), and the FCR value (2,3) suggested diminished feed efficiency, highlighting operational difficulties. The financial analysis indicated that the business is viable, evidenced by a coefficient of variation of 0,35 and a positive lower-bound income, implying modest risk yet sustained returns. The study highlights the significance of systematic risk management strategies—particularly in illness prevention, feed optimization, and DOC quality control—to guarantee farm resilience and profitability. These findings offer practical insights for smallholder farmers and policymakers aiming to enhance the broiler sector in rural Indonesia.